(untitled) (Research, Society and Development, 2020)
In this article, some reflections are made about the peasantry present in rural agrarian reform settlements in the Federal District, central region of Brazil, based on part of the author’s professional experience in his work as a rural extension worker linked to the Technical Assistance and Extension Company Rural Federal District (Emater - DF) in these communities. The chosen methodology was the “case study” and the analysis of these experiences in dialogue with the academic literature related to the topic addressed. To present these reflections on the way of life of the residents and workers of these rural settlements, practical situations involving rites and signs and their social relations in the symbolic processes that correlate the work of the land and the way of "knowing how to do" of these families.